Next-generation sequencing diagnostics of bacteremia in sepsis (Next GeneSiS-Trial): study protocol of a prospective, observational, noninterventional, multicenter, clinical trial - Brenner, Thorsten; Decker, Sebastian; Bruckner, Thomas; Schmoch, Thomas; Weigand, Markus A. (Medicine, 2018)
Background: Sepsis remains a major challenge, even in modern intensive care medicine. The identification of the causative pathogen is crucial for an early optimization of the antimicrobial treatment regime. In this context, culture-based diagnostic procedures (e.g., blood cultures) represent the standard of care, although they are associated with relevant limitations. Accordingly, culture-independent molecular diagnostic procedures might be of help for the identification of the causative pathogen in infected patients. The concept of an unbiased sequence analysis of circulating cell-free DNA (cfDNA) from plasma samples of septic patients by next-generation sequencing (NGS) has recently been identified to be a promising diagnostic platform for critically ill patients suffering from bloodstream infections. Although this new approach might be more sensitive and specific than culture-based state-of-the-art technologies, additional clinical trials are needed to exactly define the performance as well as clinical value of a NGS-based approach. Methods: Next GeneSiS is a prospective, observational, noninterventional, multicenter study to assess the diagnostic performance of a NGS-based approach for the detection of relevant infecting organisms in patients with suspected or proven sepsis [according to recent sepsis definitions (sepsis-3)] by the use of the quantitative sepsis indicating quantifier (SIQ) score in comparison to standard (culture-based) microbiological diagnostics. The clinical value of this NGS-based approach will be estimated by a panel of independent clinical specialists, retrospectively identifying potential changes in patients’ management based on NGS results. Further subgroup analyses will focus on the clinical value especially for patients suffering from a failure of empiric treatment within the first 3 days after onset [as assessed by death of the patient or lack of improvement of the patient's clinical condition (in terms of an inadequate decrease of SOFA-score) or persistent high procalcitonin levels]. Discussion: This prospective, observational, noninterventional, multicenter study for the first time investigates the performance as well as the clinical value of a NGS-based approach for the detection of bacteremia in patients with sepsis and may therefore be a pivotal step toward the clinical use of NGS in this indication.